THE ROLE AND PROSPECTS OF DIGITAL TECHNOLOGIES IN PHYSICAL EDUCATION AND SPORTS TRAINING - Eshboyev Shakhriyor Furqat ogli (Bright Mind Publishing, 2025)
This article examines the role of digital technologies in physical education and sports training, focusing on their effectiveness and application based on international experiences. It explores how digital tools can help organize lessons in an interactive, personalized, and high-quality manner, while also comparing these practices with current approaches in Uzbekistan.
Keywords: Digital technologies, physical education, sports training, virtual reality, interactive methods, international experience, remote workouts.